Laurdan generalized polarization fluctuations measures membrane packing micro-heterogeneity in vivo - Sanchez, Susana A. (2012)
Cellular membranes are heterogeneous in composition, and the prevailing theory holds that the structures responsible for this heterogeneity in vivo are small structures (10–200 nm), sterol- and sphingolipid-enriched, of different sizes, highly dynamic denominated rafts. Rafts are postulated to be platforms, which by sequestering different membrane components can compartmentalize cellular processes and regulate signaling pathways. Despite an enormous effort in this area, the existence of these domains is still under debate due to the characteristics of the structures itself: small in size and highly mobile, which from the technical point of view implies using techniques with high spatial and temporal resolution. In this report we measured rapid fluctuations of the normalized ratio of the emission intensity at two wavelengths of Laurdan, a membrane fluorescent dye sensitive to local membrane packing. We observed generalized polarization fluctuations in the plasma membrane of intact rabbit erythrocytes and Chinese hamster ovary cells that can be explained by the existence of tightly packed micro-domains moving in a more fluid background phase. These structures, which display different lipid packing, have different sizes; they are found in the same cell and in the entire cell population. The small size and characteristic high lipid packing indicate that these micro-domains have properties that have been proposed for lipid rafts.